HASIL BELAJAR KOGNITIF SISWA PADA MATERI CAHAYA MELALUI PENERAPAN MODEL ADVANCE ORGANIZER DI KELAS VIII SMPN 3 TAMBANG - Dwi Nofita Sari; Zuhdi Ma’aruf; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe students cognitive learning outcomes in light materials through the application of advance organizer learning model. This research was conucted in grade VIII SMPN 3 Tambang from March to May 2018. The subjects of this research were the students of class VIII.2 as the experimental class applying the advance organizer model and the students of class VIII.5 as the control class applying the conventional learning model. Each class consists of 27 students. This form of research is Pre-Experimental design with intact group comparison design. The instrument of data collection in this study is a cognitive larning result test consisting of 20 item of objective and given the end o treatment. Data analysis techniques using descriptive analysis. The result of descriptive analysis obtained the average absorption power of 70,93 % with is in good category and students learning result with conventional learning obtained the average absorption 65,37 % with is in good enough category. It can be concluded that learning using advance organizer model on light material is more effective in improving students cognive learning outcomes in light material class VIII SMPN 3 Tambang.Key word : Advance Organizer Model, Cognitive Learning Outcomes